Challenges and opportunities in stigma for psychiatrists - Rajasuriya, M.; Fernando, S.M.; Gunawardhana, U. (Sri Lanka College of Psychiatrists, 2015)
Stigma leads to discrimination of the patient, family, health care providers and services. A workshop-type qualitative analysis was conducted with a panel of 40 psychiatrists to attempt to apply evidence based anti-stigma strategies to five given hypothetical case vignettes. Various combinations of protest, education and challenge strategies were selected as effective by the panel. The analysis also revealed a number of stigmatising beliefs related to psychiatry as a profession and behaviour of patients. Psychiatrists themselves need to change such beliefs as part of reducing stigma related to mental illnesses.
An analysis of effective coping mechanisms to reduce stigma associated with mental illnesses
Keywords: stigma; beliefs; behaviour; discrimination; mental illness; psychiatrist